Bio-based herding and gelling agents from cholesterol powders and suspensions in organic liquids for effective oil spill clean-up - Miral Abuoudah; Adewale Giwa; Inas Nashef; Faisal AlMarzooqi; Hanifa Taher (Chemical Engineering Journal Advances, 2022)
The negative impacts of an oil spill are severe and can last for decades after the incident. The development of techniques to overcome this threat is crucial to the ecosystem as well as human lives. The herder effectiveness of different cholesterol forms, including powders and suspensions, were measured and compared by using a MATLAB code to estimate the surface area of oil spill contracted/thickened. The powders were distinguished by their particle size distributions, crystal phases, and thermal properties. Formation of gel oil aggregates was achieved by all cholesterol powders. The highest herder effectiveness of 73.3 ± 2.0% was shown by CP/D, that is, the cholesterol powder that had the lowest particle sizes of 0.5–0.99 mm, anhydrous crystal phases, and lowest thermal degradation rate of 95.4%. Cholesterol suspensions were further prepared from the mixtures of CP/D and delivery liquids, namely gasoline, toluene, and biodiesel by varying CP/D-to-solvent ratio from 1:2 to 1:4. Herding of oil spill, instead of gel oil aggregation only, was achieved by cholesterol suspensions. Biodiesel was found to be the most efficient delivery liquid, resulting in the highest herder effectiveness of 79.1 ± 0.7%. CP/D-biodiesel suspension reduced the surface tension of water from 73.5 to 28 mN/m. Optimum herder effectiveness was estimated from full factorial experimental design and Response Surface Methodology at different conditions of temperature, water salinity and agent-to-oil ratio (AOR). Analysis of variance (ANOVA) confirmed that salinity and temperature had significant effects on the herder effectiveness of CP/D-biodiesel but the effect of AOR was insignificant. The optimum herder effectiveness was 79.5% and the accuracy of this prediction was obtained as 95%. This study demonstrated that CP/D-biodiesel suspension is a promising bio-based herding agent.